The moderating role of firm size on financial characteristics and Islamic firm value at Indonesian equity market - Perdana Wahyu Santosa (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
This study aims to understand the moderating role of firm size on financial characteristics and Islamic firm value. Then study how the influence of firm size moderation on the relationship of financial characteristics and corporate governance with firm value. This study uses secondary data from financial statements and analyzed by the panel data method for six years. The sample selection is arranged by the purposive sampling method with Islamic index constituent population. Conclusion: leverage, profitability, and efficiency have a significant positive effect on Islamic firm value, but the liquidity and audit committee do not affect. Firm size moderators provide a reinforcing effect for all independent variables so that liquidity and audit committees have a positive effect on firm value. Implications: Islamic firm investors in the equity market should consider the crucial variable, namely firm size, in addition to firm and corporate governance characteristics. These conclusions provide important implications for managers and relevant authorities to enhance financial market information related to firm value and further attention to corporate governance mechanisms.
Keywords: G30; G32; 650; firm value; financial characteristics; audit committee; firm size; equity market; Islamic index